How Could This Happen? Managing Errors in Organizations (Springer International Publishing, 2018)
The first comprehensive reference work on error management, blending the latest thinking with state of the art industry practice on how organizations can learn from mistakes. Even today the reality of error management in some organizations is simple: "Don't make mistakes. And if you do, you're on your own unless you can blame someone else." In most, it has moved on but it is still often centered around quality control, with Six Sigma Black Belts seeking to eradicate errors with an unattainable goal of zero. But the best organizations have gone further. They understand that mistakes happen, be they systemic or human. They have realized that rather than being stigmatized, errors have to be openly discussed, analyzed, and used as a source for learning. In How Could This Happen? Jan Hagen collects insights from the leading academics in this field - covering the prerequisites for error reporting, such as psychological safety, organizational learning and innovation, safety management systems, and the influence of senior leadership behavior on the reporting climate. This research is complemented by contributions from practitioners who write about their professional experiences of error management. They provide not only ideas for implementation but also offer an inside view of highly demanding work environments, such as flight operations in the military and operating nuclear submarines. Every organization makes mistakes. Not every organization learns from them. It's the job of leaders to create the culture and processes that enable that to happen. Hagen and his team show you how.